Physico-chemical and Pharmacological Studies of Some Transition Metal Complexes with 2-cis-3,7-Dimethyl-2,6-Octadien-1-al - Chand, Mangal; Nagar, Meena (Asian Journal of Chemistry, 2010)
Acyclic monoterpenoids form complexes with many transition metals. 2-Cis-3,7-dimethyl-2,6-octadien-1-al (citral) form complexes with VO(II), Cr(III) and Mn(II). Stereochemistry of the complexes has been studied by physico-chemical methods. Ligand and its metal complexes have been found effective as antiprotozoal, insecticidal and antifungal. The control drugs ampicillin (10 μg/mL) and streptomycin (5 μg/mL) show 22.00 mm and 18.00 mm effective concentration respectively against E. coli and 26.00 mm and 24.00 mm against S. aureus respectively which is according to NCCLS standard.